The splicing factor SRSF6 is amplified and is an oncoprotein in lung and colon cancers. Issue 4 (15th February 2013) - Cohen‐Eliav, Michal; Golan‐Gerstl, Regina; Siegfried, Zahava; Andersen, Claus L; Thorsen, Kasper; Ørntoft, Torben F; Mu, David; Karni, Rotem
Abstract An increasing body of evidence connects alterations in the process of alternative splicing with cancer development and progression. However, a direct role of splicing factors as drivers of cancer development is mostly unknown. We analysed the gene copy number of several splicing factors in colon and lung tumours, and found that the gene encoding for the splicing factor SRSF6 is amplified and over‐expressed in these cancers. Moreover, over‐expression of SRSF6 in immortal lung epithelial cells enhanced proliferation, protected them from chemotherapy‐induced cell death and converted them to be tumourigenic in mice. In contrast, knock‐down of SRSF6 in lung and colon cancer cell lines inhibited their tumourigenic abilities. SRSF6 up‐ or down‐regulation altered the splicing of several tumour suppressors and oncogenes to generate the oncogenic isoforms and reduce the tumour‐suppressive isoforms. Our data suggest that the splicing factor SRSF6 is an oncoprotein that regulates the proliferation and survival of lung and colon cancer cells.